The Role of Eco-labels, Advertising, Price, Attitude, and Environmental Awareness in Influencing Purchasing Decisions for Environmentally Friendly Products for Generation Z in Tangerang City - Firzanah Adya Talitha; Mohamad Harisudin; Amalia Nadifta Ulfa (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Environmental damage has become an increasingly evident global threat, urging humanity to become more environmentally conscious. One effort to address this is by purchasing environmentally friendly products, such as eco-labeling bottled water. This study analyzes the influence of ecological labels, advertising, price, attitudes, and environmental awareness on Generation Z’s purchasing decisions for ecologically labeled bottled water in Tangerang City. The basic method of this study is causal-comparative. The location of the study was determined purposively, namely in Tangerang City, Banten. This study used primary and secondary data, analyzed with Structural Equation Modeling-Partial Least Square (SEM-PLS) using SmartPLS version 3. The study used an accidental sampling technique, with 150 respondents from Generation Z aged 18 to 27 who had purchased eco-labeled bottled water. The analysis results show that eco-label, price, attitude, and environmental awareness positively and significantly influence the purchasing decision of eco-labeled bottled water among Generation Z in Tangerang City. In contrast, advertising has a positive but insignificant influence. Attitude influences the purchasing decision of eco-labeled bottled water, followed by price, environmental awareness, and eco-label. Industry players should continue to innovate to create products without ignoring environmental sustainability and set optimal prices comparable to product quality. In addition, industry players need to improve communication of the benefits of ecological products through education with clear information on the packaging or eco-label campaigns.